Rancangan Laboratorum Virtual untuk Pembelajaran Fisika SMA - Masril Masril; Hidayati Hidayati; Yenni Darvina (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
One of the problems found in the implementation of the curriculum of 2013 is not all competency skills can be performed well. Therefore, to overcome these problems, virtual laboratory designed to competencies skill of physics. One of the design objectives virtual laboratory is to improve the quality of education and learning in physics in high school. The method used in this study is a research method development four D model with the definition phase , design phase , development phase, and dissemination phase. Research has reached the stage of development and has been tested valid specialist. The instrument used in the research is a questionnaire consisting of: 1) the material substance; 2) The display of visual communication; 3) instructional design; 4) the use of software; and 5) Linguistic. The results obtained to test the validity in general has been very good category (85.6), so that the design of virtual labs designed can already be used in high school.